TANTANGAN PELAKSANAAN PELAYANAN KOLABORASI TB-HIV DI RSUD DR. M. HAULUSSY AMBON - Petriana Mahmud (STIKES Pasapua Ambon, 2019)
Introduction : Tuberculosis is the cause of 20% of the 1.6 million people living with HIV and HIV is the cause of 25% of the 1.3 million TB deaths. Stop TB Partnership develop guidelines for implementing collaborative TB- HIV compiled based on the level of HIV prevalence in Indonesia. Implementing collaborative TB-HIV in Ambon began at 2015. The purpose of this research is to analyze the implementation of collaborative TB-HIV services at Dr. M. Haulussy Hospital, Ambon. Method : Descriptive analytic methods with qualitative approaches. The subject of the research was a collaborative ministry implementing TB-HIV in the Dr. M. Haulussy Ambon Hospital with 5 informant triangulation. Data collection used indepth interview and analyzed using content analysis. Result : The study showed the number of human resources in the implementation of the TB-HIV collaboration services does not meet standards. Health workers on the second unit has another position at another unit, so health workers have a duplicate work, because of the lack of health workers. Infastructure quite sufficient, just that there is some damage to the TB diagnostic tool. The output of this ministry views of some indicators of success and the result is already formed a working group on fasyankes, but the coordinator at the level of city and the province does not yet exist. Joint planning is not implemented either at the level of health services, town or province, conducted only monitoring and evaluation services that involve all health workers on both programs.